2013
DOI: 10.1128/jvi.01529-13
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Selection against Synonymous Mutations in HIV-1 env Evolution

Abstract: Intrapatient evolution of human immunodeficiency virus type 1 (HIV-1) is driven by the adaptive immune system resulting in rapid change of HIV-1 proteins. When cytotoxic CD8؉ T cells or neutralizing antibodies target a new epitope, the virus often escapes via nonsynonymous mutations that impair recognition. Synonymous mutations do not affect this interplay and are often assumed to be neutral. We test this assumption by tracking synonymous mutations in longitudinal intrapatient data from the C2-V5 part of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 47 publications
6
41
0
Order By: Relevance
“…This overall trend is consistent with the fact that synonymous mutations usually have smaller functional effects than nonsynonymous mutations. However, synonymous mutations can sometimes have substantial effects [21, 8082], particularly in viruses like HIV that are under strong selection for RNA secondary structure and codon usage [83, 84]. To assess selection on synonymous mutations on a more site-specific level, we examined the change in frequency of multi-nucleotide codon mutations across env ’s primary sequence (Fig 4).…”
Section: Resultsmentioning
confidence: 99%
“…This overall trend is consistent with the fact that synonymous mutations usually have smaller functional effects than nonsynonymous mutations. However, synonymous mutations can sometimes have substantial effects [21, 8082], particularly in viruses like HIV that are under strong selection for RNA secondary structure and codon usage [83, 84]. To assess selection on synonymous mutations on a more site-specific level, we examined the change in frequency of multi-nucleotide codon mutations across env ’s primary sequence (Fig 4).…”
Section: Resultsmentioning
confidence: 99%
“…While it has previously been suggested that HIV-1 RNA structure might constrain variability and evolution (72)(73)(74), silent mutations introduced into some of the most highly conserved RNA hairpins in HIV-1 result in no significant virus replication defects (75). Similarly, introduction of synonymous mutations into other regions of the HIV-1 genome with apparently strong purifying selection against synonymous substi- tutions does not reduce viral fitness in vitro (76).…”
Section: Discussionmentioning
confidence: 99%
“…Weak selection acting upon synonymous mutations has been identified for codon usage in influenza [45] and against mutations that disrupt RNA structure in HIV [46], although the magnitude of selection inferred here is significantly higher than in either case. While inferring the presence of selection, our method cannot match occurrences of selection to specific biological mechanisms; further data would generally be required to do this.…”
Section: Discussionmentioning
confidence: 54%